2016
DOI: 10.3892/etm.2016.3586
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effect of total saponins of Rhizoma Dioscorea nipponica on collagen induced-arthritis in rats

Abstract: Abstract. Rheumatoid arthritis (RA) is a common chronic autoimmune and incurable disease. The aim of the present study was to investigate the therapeutic effect and mechanism of the total saponins of Rhizoma Dioscorea nipponica (TSRDN) in RA. A collagen induced-arthritis (CIA) rat model was established. CIA rats were randomly divided into three groups and lavaged with an equal volume of solvent (CIA group), TSRDN (25 mg/kg/day, RDN group) and tripterygium (TP; 12 mg/kg/day, TP group) for 21 days, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…SG from Dioscorea spp. were also shown to be efficient in cardiology to treat acute myocardial infarction and enhance heart regeneration processes [8][9][10][11][12]. In Agronomy 2021, 11, 394 2 of 15 addition, SG affect human and animal reproductive systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…SG from Dioscorea spp. were also shown to be efficient in cardiology to treat acute myocardial infarction and enhance heart regeneration processes [8][9][10][11][12]. In Agronomy 2021, 11, 394 2 of 15 addition, SG affect human and animal reproductive systems [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dioscoreae Nipponicae Rhizoma (DNR), the dried rhizome of Dioscorea nipponica Makino, is widely distributed in China, South Korea, and Russia, and has been used as a traditional herbal medicine for relieving cough and asthma, eliminating rheumatic aches, alleviating pain, and improving blood circulation [1]. Modern pharmacological studies have discovered that DNR possesses anti-tumor, anti-inflammatory, anti-diuretic, analgesic, anti-tussive, immunoregulatory, and cardiovascular properties [2][3][4][5][6]. Phytochemical studies disclosed that steroidal saponins, such as protodioscin, protogracillin, pseudoprotodioscin, and pseudoprotogracillin are the major bioactive constituents in DNR, which are mainly responsible for most of the pharmacological effects of this herbal medicine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental model of collagen-induced RA in rats, the total saponins from Rhizoma dioscoreae Nipponicae increase the expression of the vascular endothelial growth factor, angiopoietin, and endothelial tyrosine kinase receptor. These results showed that the saponins inhibits angiogenesis in RA, leading to a better prognosis [55,67]. Total saponins from Psammosilene tunicoids also demonstrated activity in combating RA inflammation through downregulation of IL-1β and TNF-α.…”
Section: Saponinsmentioning
confidence: 91%